Landslide Risk Assessment for Designing Monitoring and EarlyWarning System - Teuku Faisal Fathani; Tuan Anh Bui; Wahyu Wilopo (Geological Engineering Department Universitas Gadjah Mada, 2019)
Landslide is the most frequent natural disaster in Yogyakarta, Indonesia. In the mid-March 2018, a few cracks appeared in the north of the hill in the Pendoworejo Village, Kulon Progo District, Yogyakarta Special Province. The landslide movement of this area still threatens the residents and makes them evacuated due to their fear upon potential landslide disaster. In order to reduce the risk, landslide investigation and risk assessment were conducted. The stability analysis focused on the relationship of the displacement,the velocity and the fluctuation of groundwater level due to the rainfall intensity. Then, a monitoring and warning system was designed as a non-structural mitigation effort. Based on the preliminary investigation on April 2018, there was no evidence of mass movement on the west and south part of the hill. On the other hand, the north part area was estimated to have risk as indicated by the occurrence of many cracks. Based on the result of analysis, the fluctuation of the groundwater level rose or dropped substantially before and after heavy rainfall. In the rainy season, the velocity and the displacement increased slightly in the first three months and grew rapidly afterward. In fact, the landslide risk increased in every rainy season. Therefore, the risk could be more dangerous in the future.